1999
DOI: 10.1530/eje.0.1400201
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin production is increased in normal human pregnancy

Abstract: Objective: Adrenomedullin, a recently discovered vasoactive peptide originally identified in pheochromocytoma, has been found to be increased in the plasma of pregnant women at term. This study was designed to elucidate whether adrenomedullin secretion is dependent on gestational age and the possible source and function of this peptide in human pregnancy. Study design: Adrenomedullin concentrations were determined by RIA in amniotic fluid and maternal plasma obtained from 110 pregnant women between 8 and 40 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 28 publications
1
42
2
Order By: Relevance
“…However, a recent report revealed no significant difference in mean maternal plasma concentrations of AM from week 8 to week 40 of pregnancy (14). The probable reasons for this discrepancy are the different hAM antibodies used in the RIAs, and the wide standard deviation of hAM concentrations as a result of the small sample size of our study.…”
Section: Discussioncontrasting
confidence: 71%
“…However, a recent report revealed no significant difference in mean maternal plasma concentrations of AM from week 8 to week 40 of pregnancy (14). The probable reasons for this discrepancy are the different hAM antibodies used in the RIAs, and the wide standard deviation of hAM concentrations as a result of the small sample size of our study.…”
Section: Discussioncontrasting
confidence: 71%
“…9,10 We and others have shown a progressive increase in maternal plasma ADM levels throughout pregnancy. [11][12][13][14][15][16] In PE, early reports suggested that maternal ADM levels were decreased, but subsequent larger series found no difference from controls. 14,17,18 However, we believe that this indicates a lack of compensatory increase in response to the hypertensive state.…”
mentioning
confidence: 99%
“…The concentration of ADM in maternal plasma increases during pregnancy in the human. 16,17 Furthermore, fetoplacental tissues appear to be an additional site of synthesis of ADM during pregnancy. 18 The role of ADM in the pathophysiology of preeclampsia is complex.…”
mentioning
confidence: 99%